Kenya’s 2017 Basic Education Curriculum Framework: A Comprehensive Review - Heto, Prince Paa-Kwesi; Odari, Masumi H.; Sunu, Wyse (Journal of Interdisciplinary Studies in Education, 2020)
Kenya’s 2017 competency-based curriculum, the Basic Education Curriculum Framework (BECF), seeks to address the skills gap in the education system and make the curriculum relevant to learners. Using Soka education as the philosophical framework, we provide a comprehensive review of BECF. The analysis in this essay covers the noteworthy provisions, double-edge policies, inconsistencies, issues of concern, and potential hurdles to implementation. It argues that the curriculum is not likely to produce the intended outcome due to inherent contradictions in the framework and the lack of an effective implementation plan. While BECF provides a broad and ambitious roadmap for the transformation of the Kenyan education system, actualizing the bold vision of BECF will require an extensive overhaul of the education system, a herculean task